Facile synthesis of ultrathin two-dimensional nanosheets-constructed MCo2O4 (M = Ni, Cu, Zn) nanotubes for efficient photocatalytic oxygen evolution. Issue 8 (8th February 2018) - Ding, Erli; Li, Ali; Liu, Hanwen; Liu, Weisheng; Chen, Fengjuan; Li, Tianrong; Wang, Baodui
Abstract : A simple and versatile approach was developed to synthesize hierarchical nanosheets-constructed MCo2 O4 (M = Ni, Cu, Zn) nanotubes. The resultant nanotubes exhibited high photocatalytic activity toward water oxidation reaction. Abstract : Hierarchical nanosheets-assembled nanotubes are of great interest for their unique physicochemical properties as well as their potential applications in a variety of fields. However, the synthesis of hierarchical mixed transition-metal oxides-based nanosheets-assembled nanotubes for highly efficient photocatalytic oxygen evolution is rarely reported. Herein, a simple and versatile approach was developed to synthesize hierarchical nanosheets-constructed MCo2 O4 (M = Ni, Cu, Zn) nanotubes. Core–shell polyacrylonitrile (PAN)/M-cobalt hydroxide ultrathin nanosheet composite nanofibers were first synthesized by hydroxylation reaction between PAN/M-cobalt acetate hydroxide precursors and NaBH4 . After calcination, these nanofibers as precursors were easily transformed into the corresponding hierarchical nanosheets-constructed MCo2 O4 nanotubes. By applying a photocatalyst, the resultant MCo2 O4 nanotubes, particularly the CuCo2 O4 nanotubes, exhibited high photocatalytic activity and cycle stability toward water oxidation reaction with O2 generation rates of 51.1 mmol g −1 h −1 under visible light irradiation, which is higher than most reported catalysts. This approach is very versatile and can be applied to synthesize other hierarchical multi-element oxides-based nanosheets-constructed nanotubes for advanced applications.